Swine Breeding Investigations - Koch, B.A. (Kansas Agricultural Experiment Station, 2011)
A crossbred barrow sired by a Duroc boar (University Charm 16753), and out of a Poland China sow (Prince’s Maiden 20-521492), was first place crossbred barrow at the 1962 Kansas State Fair. The barrow produced the champion carcass when slaughtered.
Keywords: Swine; Champion carcass; Carcass data